Value Attitudes of Mothers in Modern Parenthood Models - Avdeeva, N.N.; Berseneva, I.V. (Socialʹnaâ Psihologiâ i Obŝestvo, 2022)
Objective. Comparative analysis of mothers’ value attitudes in different models modern parenting (“natural”, “intensive”). Background. Modern parents face new social challenges: the competition of family values, parenthood and career building; difficulties in adapting to a rapidly changing world; uncertainty cultural patterns of raising children in the family, which lead to the search for new strategies and practices of family education. Study design. In the work, value attitudes were determined and compared mothers of preschool children in two models: “natural” and “intensive” parenting. Statistical processing of the obtained data was carried out using the Pearson’s χ2 criterion, the Mann-Whitney U-criterion. Participants. The study involved 50 mothers preschoolers aged 30 to 40 years, married, with higher education. The research base. Internet platforms: thematic forums, social networks and groups (“Mother and child”, “Natural development”, “Intensive education”, “Conscious parenting”). Measurements. The author’s questionnaire aimed at identifying the model of parenthood (I.V. Ber-seneva, N.N. Avdeeva); 2) The methodology of M. Rokich’s “Value orientations”. 3) The author’s ques-tionnaire “Conditions of upbringing and development of the child”. Results. For mothers inclined to the “intensive” parenting model, priority value orientations: financially secure life; the ability to think sensibly and logically, make deliberate, rational decisions; the opportunity to improve your level of education, intellectual development, culture; self-control; accuracy; discipline. For mothers who adhere to the “natural” parenting model — life experience, courage in defending their opinions, sensitivity, independence in judgments and actions, tolerance, self-realization in household management. Сonclusions. The specificity of the relationship between the value orientations of mothers and the model of parenthood is revealed. It is shown that there are both similarities and differences hierarchies of value orientations among mothers who adhere to the “intensive” and “natural” models of parenthood. The revealed patterns are consistent with studies of parenting models in foreign psychology and reflect the strategies of parents’ search for effective parenting strategies in a rapidly changing world. Цель. Сравнительный анализ ценностных установок матерей в разных моделях родительства («естественное», «интенсивное»). Контекст и актуальность. Современные родители сталкиваются с новыми социальными вызовами: конкуренция ценностей семьи, родительства и построения карьеры; трудности адаптации к быстро меняющемуся миру; неопределенность культурных образцов воспитания детей в семье, что приводит к поиску новых стратегий и практик семейного воспитания. Дизайн исследования. В работе определялись и сравнивались ценностные установки матерей детей дошкольного возраста в двух моделях: «естественного» и «интенсивного» родительства. Статистическая обработка полученных данных осуществлялась при помощи критерия χ2 Пирсона, U-критерия Манна-Уитни. Участники. В исследовании приняли участие 50 матерей дошкольников в возрасте от 30 до 40 лет, состоящих в браке, имеющих высшее образование. База исследования. Интернет-площадки: тематические форумы, социальные сети и группы («Мать и ребенок», «Естественное развитие», «Интенсивное воспитание», «Осознанное родительство»). Методы (инструменты). 1) Авторский опросник, направленный на выявление модели родительства (И.В. Берсенева, Н.Н. Авдеева); 2) Методика М. Рокича «Ценностные ориентации»; 3) Авторская анкета «Условия воспитания и развития ребенка». Результаты. Для матерей, склонных к модели «интенсивное» родительство, приоритетные ценностные ориентации: материально обеспеченная жизнь; умение здраво и логически мыслить, принимать обдуманные, рациональные решения; возможность повышать свой уровень образования, интеллектуального развития, культуры; самоконтроль; аккуратность; дисциплинированность. Для матерей, придерживающихся модели «естественное» родительство, — жизненный опыт, смелость в отстаивании своего мнения, чуткость, независимость в суждениях и поступках, терпимость, самореализация в ведении домашнего хозяйства. Основные выводы. Выявлена специфика связи ценностных ориентаций матерей и модели родительства. Показано, что существует как сходство, так и различие в иерархии ценностных ориентиров у матерей, придерживающихся «интенсивной» и «естественной» моделей родительства. Выявленные закономерности согласуются с исследованиями моделей родительства в зарубежной психологии и отражают стратегии поиска родителями эффективных стратегий воспитания в быстро меняющемся мире.